The TriForC database: a comprehensive up-to-date resource of plant triterpene biosynthesis. Issue Volume 46:Issue D1(2018) (17th October 2017) - Miettinen, Karel; Iñigo, Sabrina; Kreft, Lukasz; Pollier, Jacob; De Bo, Christof; Botzki, Alexander; Coppens, Frederik; Bak, Søren; Goossens, Alain
Abstract: Triterpenes constitute a large and important class of plant natural products with diverse structures and functions. Their biological roles range from membrane structural components over plant hormones to specialized plant defence compounds. Furthermore, triterpenes have great potential for a variety of commercial applications such as vaccine adjuvants, anti-cancer drugs, food supplements and agronomic agents. Their biosynthesis is carried out through complicated, branched pathways by multiple enzyme types that include oxidosqualene cyclases, cytochrome P450s, and UDP-glycosyltransferases. Given that the number of characterized triterpene biosynthesis enzymes has been growing fast recently, the need for a database specifically focusing on triterpene enzymology became eminent. Here, we present the TriForC database (http://bioinformatics.psb.ugent.be/triforc/ ), encompassing a comprehensive catalogue of triterpene biosynthesis enzymes. This highly interlinked database serves as a user-friendly access point to versatile data sets of enzyme and compound features, enabling the scanning of a complete catalogue of experimentally validated triterpene enzymes, their substrates and products, as well as the pathways they constitute in various plant species. The database can be accessed by direct browsing or through convenient search tools including keyword, BLAST, plant species and substructure options. This database will facilitate gene mining and creating genetic toolboxes for triterpene synthetic biology.